Factorisation using common factors

Factorization by common factors

Ex 12.1, 1 (i)

Ex 12.1, 1 (ii)

Ex 12.1, 1 (iii) Important

Ex 12.1, 1 (iv) Important

Ex 12.1, 1 (v) You are here

Ex 12.1, 1 (vi) Important

Ex 12.1, 1 (vii)

Ex 12.1, 1 (viii) Important

Example 2 Important

Example 1

Ex 12.1, 2 (i)

Ex 12.1, 2 (ii) Important

Ex 12.1, 2 (iii)

Ex 12.1, 2 (iv) Important

Ex 12.1, 2 (v)

Ex 12.1, 2 (vi)

Ex 12.1, 2 (vii)

Ex 12.1, 2 (viii) Important

Ex 12.1, 2 (ix)

Ex 12.1, 2 (x) Important

Last updated at April 16, 2024 by Teachoo

Ex 12.1, 1 Find the common factors of the given terms. (v) 6 𝑎𝑏𝑐, 〖24𝑎𝑏〗^2,〖12𝑎〗^2 𝑏 6𝒂𝒃𝒄 = 6 × 𝑎𝑏𝑐 = 2 × 3 × 𝑎𝑏𝑐 = 2 × 3 × 𝒂 × 𝒃 × 𝒄 24〖𝒂𝒃〗^𝟐 = 24 × 〖𝑎𝑏〗^2 = 2 × 2 × 2 × 3 × 𝑎𝑏^2 = 2 × 2 × 2 × 3 × 𝒂 × 𝒃 × 𝒃 12𝒂^𝟐 𝒃 = 12 × 𝑎^2 𝑏 = 2 × 2 × 3 × 𝑎^2 𝑏 = 2 × 2 × 3 × 𝒂 × 𝒂 × 𝒃 So, 6 𝒂𝒃𝒄 = 2 × 3 × 𝑎 "× " 𝑏 × 𝑐 24 𝒂𝒃^𝟐 = 2 × 2 × 2 × 3 × 𝑎 "× " 𝑏 × 𝑐 12 𝒂^𝟐 𝒃 = 2 × 2 × 3 × 𝑎 × 𝑎 × 𝑏 So, Common factor = 2 × 3 × 𝑎 × 𝑏 = 6 × 𝑎𝑏 = 6𝒂𝒃